Capital Structure, Cost of Debt and Dividend Payout of Firms in New York and Shanghai Stock Exchanges - Jiang, Jun; Jiranyakul, Komain (International Journal of Economics and Financial Issues, 2012)
The Study collects panel data of listed firms in New York Stock and Shanghai Stock Exchanges during 1992 to 2008. The data are used to perform panel regression estimates for firms in each stock market. The main purpose is to compare the decision on dividend payout of listed firms in the two stock markets. The results from fixed effect estimates show that factors that can explain dividend payout of firms in New York Stock Exchange poorly explain dividend payout of firms in Shanghai Stock Exchange. This paper adds to the literature in that it provides an evidence of difference in dividend policy of firms between advanced and emerging stock markets. For policymakers in the Chinese economy, implementation of measures to enhance the advancement of bond market is necessary. Additionally, firms in Shanghai Stock Exchange should adjust their capital structure to provide room for investors to diversify and adjust their portfolios of stocks and bonds. Keywords: Dividend payout; debt financing; equity financing; cost of debt; panel regression; stock markets JEL Classifications: G35; G30